PERAN HUMOR GURU DALAM MENINGKATKAN SEMANGAT BELAJAR SISWA KELAS VI DI SD LABSCHOOL UNNES - Adriannuh, Falah; Setiawan, Deni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the use of humor as a pedagogical strategy in classroom learning for sixth-grade students at SD Labschool UNNES. The study employed a qualitative approach with a descriptive method through classroom observations, teacher interviews, and student questionnaires. The research subjects consisted of one sixth-grade teacher and 21 students. The findings indicate that the teacher used humor contextually at various stages of the learning process to create a relaxed classroom atmosphere, maintain students’ attention, and support students’ understanding of learning materials perceived as difficult. The forms of humor used included spontaneous humor, planned humor, and situational humor adjusted to the learning materials, classroom conditions, and students’ characteristics. Students’ perceptions of the use of humor showed positive responses, with most students stating that teachers’ humor created a pleasant learning atmosphere and increased learning motivation, thereby supporting student engagement in learning.